El Salvador Financial Sector Assessment Program Update : Public Banks - International Monetary Fund; World Bank (Washington, DC, 2017)
The global financial crisis and ensuing credit crunch has revived the discussion on the role of public sector in the financial system around the world and in El Salvador, authorities have announced plans to step up their activities. A clearly defined strategy for the public banks, focused on complementing private sector activity, is necessary as their activities expand to improve access to finance and diversify the sources of funding. Any process of growth needs to accompany by improvement in risk management processes, governance arrangements and enhanced supervision. Going forward, the two public retail banks should increase their specialization in different market segments. The development bank role can be enhanced while maintaining its second tier status. To make the guarantee funds effective, in addition to scale their size, several operational features need to be improved.